Sustainable Business Strategy Analysis, Choice and Implementation - Grantham, Andrew (de Gruyter, 2022)
"In the twenty-first century, there is no single prescription for business strategy development, choice and implementation. The challenges facing firms, not-for-profit organizations and the public sector are significant and call for creativity, inclusivity, diversity and responsibility. The looming and deepening crisis of climate change, imperatives of the UN Sustainable Development Goals and global pandemics, have exposed the risks associated with an exclusive market worldview and the indicators that drive it such as GDP, stock market values, return on investment, executive remuneration, etc. Sustainable Business Strategy augments and challenges existing texts to offer a progressive, challenging, decolonized and plural business strategy curriculum. Andrew Grantham presents existing business strategy theories, tools and techniques, introduces contemporary critiques, and offers fresh thinking about the application of the models and outcomes. The book takes the position that what we know about strategic analysis, choice and implementation needs updating and revision; while there remains a significant role for the market in a healthy, sustainable and future-oriented economy, strategic decisions will be mediated by regulation, broad stakeholder engagement and planetary boundaries. This book is written to be used as a core text for students studying business or corporate strategy at undergraduate and master's levels. The author uses contemporary examples by way of illustration but seeks to guide readers to investigate the case in greater detail for themselves using references and hyperlinks. Questions and exercise sections in each chapter can be utilized in seminar classes and/or assessments."--